The Free Speech Movement : reflections on Berkeley in the 1960s - Cohen, Robert, 1955 May 21-; Zelnik, Reginald E. (University of California Press, 2002)
An examination of Berkeley's celebrated Free Speech Movement (FSM) of 1964. Drawing from the experiences of many movement veterans, this collection of scholarly articles and personal memoirs illuminates one of the most important events in the recent history of American higher education.